Bibliometric Analysis of Publication Trends in Family Firms’ Social Capital in Emerging Economies - Nordin, Norfarah; Abdul Khalid, Siti-Nabiha; Ale Ibrahim, Nader; Samsudin, Mohd Ali (Journal of Entrepreneurship, Business and Economics, 2020)
There is a wide collection of journal articles and academic discourse on family firms’ social capital. However, the focus on the comprehensive synthesis of the collections is limited. The lack of efforts to synthesize the issue of family firms’ social capital focuses on emerging economies further limiting the utility of the literature. Despite the various differences between family firms in developed and emerging economies; no attempt was undertaken to separate the different insights and issues between the two different contexts. Thus, this article focusing on emerging economies is an attempt to bridge this gap in the literature. Consequently, to provide a review on researches that focus on family firm’s social capital in emerging economies, Bibliometric analysis is used to provide quantitative insights. The qualitative insights are generated from a systematic literature review. Journal articles are retrieved as data to achieve these objectives. The time frame of literature extraction is from 1960 to the year 2018. Data is extracted from WOS and Scopus indexed database yielding 288 documents. After manual scrutinizing the content, only 31 (10.8%) of the cited literature is on the family firm social capital related issue. The paper finds that there is an increasing trend in the number of family firms’ social capital study in the context of the emerging economies. The highly cited articles are published by Deephouse and Jaskiewicz (2013) in the Journal of Management Studies with 179 citations, and Khavul et al. (2009) in the Entrepreneurship: Theory and Practice with 140 citations. The findings provide a collection of evidence about the focus, variables, and theories used from credible sources of the family firms’ social capital studies. Research paper Keywords: Social capital; socioemotional wealth; family firm; emerging economies; Bibliometric; systematic review  Reference to this paper should be made as follows: Nordin, N., Abdul Khalid, S., Ale Ibrahim, N., & Samsudin, M. A. (2020). Bibliometric Analysis of Publication Trends in Family Firms’ Social Capital in Emerging Economies, Journal of Entrepreneurship, Business and Economics , 8 (1), 144–179